A general energy based fatigue failure criterion for the carbon epoxy composites. (1st March 2020) - Mandegarian, Sepanta; Taheri-Behrooz, Fathollah
Abstract: A normalized energy-based fatigue failure criterion, which employs off-axis stress and strain components to compute strain energy during cyclic loading, is presented in the current research. The new model is capable of predicting the fatigue life of unidirectional laminates subjected to tension-tension, compression-compression and tension-compression loading in any arbitrary fiber orientation. Furthermore, the proposed model is used to predict the fatigue life of multidirectional composite laminates under different cyclic loading conditions, including various stress ratios. The model is validated by the experimental data of unidirectional, cross-ply, angle-ply and multidirectional carbon/epoxy composite laminates taken from the literature. In the unidirectional and multidirectional laminates effect of fiber orientation and stress ratio are diminished, respectively. The suggested fatigue model is capable of predicting the fatigue life of angle-ply and cross-ply laminates using limited experimental data. Nonetheless, it does not result in good accuracy for multidirectional laminates with arbitrary lay-up sequence under compression-dominant loadings.